Benefits of two or more senior microsurgeons operating simultaneously in microsurgical breast reconstruction: Experience in a swedish medical center. Issue 5 (24th February 2016) - Gösseringer, Nina; Mani, Maria; Cali‐Cassi, Lorenzo; Papadopoulou, Antonia; Rodriguez‐Lorenzo, Andres
Abstract : Background: The aim of this study is to evaluate how the number of senior microsurgeons, performing autologous microvascular breast reconstruction together, influences operating time and postoperative complications. Methods: A retrospective study was carried out in one hundred consecutive patients who underwent unilateral delayed deep inferior epigastric perforator flap reconstruction at a single institution. All patients followed our institution's surgical protocol and were divided into groups depending on the number of senior microsurgeons that simultaneously performed the procedure. Operating time and complications were compared between the groups. Results: Sixteen of the patients were operated by one single microsurgically trained specialist, 64 by two and 20 by three specialists. The mean operating time for the one microsurgeon's group was 286 ± 84 min, for the two‐microsurgeons' group 265 ± 57 min and for the three‐microsurgeons' group 251 ± 59 min. There was a trend of decreasing operating times when more microsurgeons performed surgery together, however the difference between groups was not statistically significant ( P = 0.251). Total flap failure rate was 2% (2/100). Both cases occurred in the group operated by one single microsurgeon (2/16) compared with two microsurgeon's group (0/64) and three microsurgeon's group (0/20; P < 0.005). Conclusions: By optimising the surgical experience available during microvascular breast reconstruction, operating time can be reduced and efficiency improved. In the current setting, two microsurgically trained surgeons achieved optimal operation flow with the lowest complication rate. © 2016 Wiley Periodicals, Inc. Microsurgery 37:416–420, 2017.